Tax and Pension Reform in the Czech Republic-Implications for Growth and Debt Sustainability - Botman, Dennis (IMF Working Papers; Working Paper ;, 2008)
The Czech Republic has embarked on an ambitious tax reform and expenditure package to bring the deficit sustainably below 3 percent, and intends to reduce the deficit to 1 percent of GDP by 2012. To address the long-term fiscal challenge due to population aging, pension reform proposals are also being considered. In this paper we assess the macroeconomic effects of these measures using the Global Fiscal Model. The tax reform package will achieve a more efficient tax system. If implemented successfully with the intended expenditure savings measures, debt is projected to improve markedly while output would expand. Fiscal sustainability will not be restored, however, even if further measures to bring the deficit to 1 percent of GDP by 2012. Instead, raising the retirement age and prefunding future aging costs would be needed to keep debt below 60 percent of GDP through 2050.